The Impact of cartels on the poor (UN New YorkUS, 2013)
Reviews a number of cartel cases from various jurisdictions in sectors which are most likely to affect the poor. It identifies the common features of these cartels and the challenges involved in detecting and prosecuting them by young competition agencies.
Keywords: COMPETITION